Recommendation on semantic web pages based on conceptual prediction model - Jenila R, Blessy; S, Bharathi (International Journal of Engineering and Technology, 2018)
The development of trhe web has made a major test for guiding the client to the pages in their regions.Useful knowledge disclosure from web use information and acceptable learning portrayal for successful page suggestion are urgent and testing.In this paper we propose a novel technique to effectively give a better site page proposal through semantic upgrade by coordinating the space and web use learning of a site.Two new models are proposed to the learning.Semantic system is used to the web pages and the relations between the pages.Conceptional model produces a semantic system for web use information,which is the combination of learning and web use information.Various inquires have been created to inquiry about these learning base.Based on these questions ,an arrangement of suggestion methodologies have been proposed to produce fitting site page proposals to the client.The suggestion comes about have been contrasted and the outcomes got from a progressed existing Web Usage Mining(WUM)strategy.The exploratory outcomes show that the proposed technique delivers essentialy higher execution than the WUM technique.